ITAL Editorial Board Thoughts: Events in the Life of ITAL - Farnel, Sharon (Information Technology and Libraries, 2018)
In this, my last Editorial Board Thoughts piece as I end my time on the ITAL Board, I use data gathered through the Crossref Event Data service to give a snapshot of citations, references, and tweets in the life of ITAL.